The Combination of Steganography and Cryptography for Medical Image Applications - B. Kiran Bala; R. Sasi Kumar (International Journal of Advances in Applied Sciences, 2018)
To give more security for the biomedical images for the patient betterment as well privacy for the patient highly confidently patient image report can be placed in database. If unknown persons like hospital staffs, relatives and third parties like intruder trying to see the report it has in the form of hidden state in another image. The patient detail like MRI image has been converted into any form of steganography. Then, encrypt those image by using proposed cryptography algorithm and place in the database.